A Close Examination of the 2016 Dallas and Baton Rouge Police Killers: Identifying Potential Risk Factors and Influences for Copycat Violence - Lankford, Adam (International criminal justice review, 2023)
Two of the worst targeted attacks on American police officers in recent history occurred within eleven days of each other. Although it seems clear their proximity was not merely attributable to chance, the connection between these incidents, and the implications for understanding copycat violence, have never been fully explored. This study analyzes the perpetrators of these attacks from a “thresholds of violence” perspective, which suggests the first actor in a sequence is more likely to be disturbed and violence prone, while subsequent actors are typically less disturbed but more socially influenced. Results suggest the thresholds model has both merits and limits. The first attacker did have more psychological problems and violence in his past, and the second did seem more influenced by violent role models. However, there were also many similarities between them, and both attacked due to a combination of internal and external factors. If this study's findings are generalizable, higher risks of becoming a copycat offender may exist for individuals who have (1) personal similarities with previous attackers, (2) a history of psychological problems, (3) a history of interest in violent actors, and (4) recent escalation in their online behavior. Recommendations are offered for future research, offender profiling, and violence prevention.